Education And Eating Pattern As Risk Factors Of Diabetes Mellitus - Ninna Rohmawati (Pancaran Pendidikan, 2017)
Education and eating pattern has significant contributions in determining incident of Diabetes Mellitus. Based on Riskesdas 2013, patient of Diabetes Mellitus who age >15 years increased from 5.7% (2007) to 6.9% (2013). Prevalence of Diabetes Mellitus in east java diagnosed by a doctor at 2.1%. The aim to determine risk factors affecting Diabetes Mellitus. This research was observational study. Subjects were patient of type 2 Diabetes Mellitus in RSD Kalisat who fulfilled inclusion criteria. Research subjects consisted of 40 people. Risk factors patients type 2 diabetes mellitus in the work area of Kalisat hospital Jember regency was in majority 45 years (82.5%), female (62.5%), basic education (77.5%), low levels of knowledge (47.5%), housewives 45%, eating pattern (87.5%), less sport activity (67.5%), less physical activity (55% ), overweight (37.5%) and not have the acts of hypertension (55%). Advice: education relation to knowledge needs to be improved, have good eating pattern, and need for regular physical activity.